Jesus Christ : Savior & Lord - Bloesch, Donald G., 1928-2010. (Downers Grove, Ill. : InterVarsity Press, 1997)
"With his customary encylopedic reach and epigrammatic style, Donald Bloesch turns to the hotly disputed, yet absolutely crucial, theological subject of the person and work of Jesus Christ. This volume includes illuminating discussion of humanity's plight, the Incarnation, the virgin birth, the relation between law and gospel, and the lordship and finality of Christ."--Jacket.
1. Christ in Dispute -- 2. The Plight of Humanity -- 3. The Mystery of the Incarnation -- 4. The Virgin Birth -- 5. The Preexistence of Jesus Christ -- 6. Christ's Atoning Sacrifice -- 7. Salvation in Evangelical Protestantism -- 8. Law and Gospel: A Reformed Perspective -- 9. The Lordship of Christ in Theological History -- 10. The Finality of Christ.
Includes bibliographical references (pages 250-296) and indexes.
Keywords: Jesus Christ -- Person and offices; Jesus Christ - Person and offices; Jesus Christ - History of doctrines